OBITUARIES ZAHIDA BANO - Editor (Hamdard Islamicus, 2021)
We announce, with deep sorrow, the passing of a quiet but strong pillar of Hamdard Pakistan: Zahida Bano Sahibah, Director of English Publications. (To Allah [s.w.t.] we belong and to Allah [s.w.t.] is our return).